Legal Protection of Trade Secrets in a Business Portfolio Against Misuse by Former Employees: An Analysis of Judgment No. 1035/Pdt.G/2022/Pn.Jkt.Pst - Henni Wijayanti; Syaela Rizkiah (Ridwan Institute, 2026)
In the rapidly evolving digital economy, business information such as marketing strategies, product designs, customer databases, and project portfolios possesses significant economic value due to its capacity to provide competitive advantages for business actors. This study analyzes the legal protection of Trade Secrets concerning the Van Houten Portfolio owned by PT Flux Asia Solusindo, which was unlawfully used by its former employee, as well as examines the application of law by the judges in Decision Number 1035/Pdt.G/2022/PN.Jkt.Pst. This research employs a normative juridical method using a statutory and case approach. The findings indicate that the defendant’s actions fulfilled the elements of trade secret infringement as stipulated under Article 13 of Law Number 30 of 2000 on Trade Secrets, as well as the elements of an unlawful act pursuant to Article 1365 of the Indonesian Civil Code. However, the judges’ consideration, which relied solely on Article 1365 of the Civil Code as the legal basis for the decision, does not fully reflect the application of the principle of lex specialis derogat legi generali, whereby specific legal provisions should prevail over general provisions.